2022
DOI: 10.1186/s12887-022-03785-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical and mental health status of orphan children living in orphanages in Sonitpur district of Assam: a cross-sectional study

Abstract: Background Orphan children living in orphanages are often neglected. These children's physical and mental health status is essential as they are highly prone to malnourishment and psychosocial distress. We aim to evaluate the orphan children's physical and psychosocial status living in orphanages. Methods This study adopted a cross-sectional research design conducted with the children living in the orphanages using a pretested, predesigned schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This study not only supports findings from previous works reporting feelings of stigmatization among the children ( 37 , 38 ), but it also shows how this contributes to the stigmatization of the children. Previous studies ( 39 , 40 ) have identified orphanage children and adolescents with emotional issues such as post-traumatic disorders. These early experiences of trauma could set the stage for the diverse emotional problems that are identified among children living within orphan homes in their later years.…”
Section: Resultsmentioning
confidence: 99%
“…This study not only supports findings from previous works reporting feelings of stigmatization among the children ( 37 , 38 ), but it also shows how this contributes to the stigmatization of the children. Previous studies ( 39 , 40 ) have identified orphanage children and adolescents with emotional issues such as post-traumatic disorders. These early experiences of trauma could set the stage for the diverse emotional problems that are identified among children living within orphan homes in their later years.…”
Section: Resultsmentioning
confidence: 99%
“…In Shukla et al (2011), the highest percentage of children (29%) fell within the age group of 13-14 years [15] . Mahanta et al (2022), reported that the majority (49.4%) of orphans belonged to the 10-14 age group [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Perkembangan anak secara keseluruhan dipengaruhi oleh masalah perilaku dan mental, yang mungkin berdampak negatif pada hasil akademis dan sosial mereka saat dewasa. 8 Penelitian mengenai kesehatan mental pada anak-anak panti asuhan di Semarang belum pernah dilakukan sebelumnya. Sehubungan dengan hal itu, penelitian ini memiliki tujuan untuk melakukan evaluasi kesehatan mental pada anak-anak yang tinggal di Panti Asuhan Kristen X, Semarang.…”
Section: Pendahuluanunclassified